The relationship between weight gain during chemotherapy and outcomes in patients with advanced non‐small cell lung cancer - Eric J. Roeland; Florian J. Fintelmann; Fiona Hilton; Ruoyong Yang; Ed Whalen; Lisa Tarasenko; Roberto A. Calle; Philip D. Bonomi (Wiley, 2024)
Abstract Background This post hoc, pooled analysis examined the relationship between different weight gain categories and overall survival (OS) in patients with non‐small cell lung cancer (NSCLC) receiving first‐line platinum‐based chemotherapy. Methods Data were pooled from the control arms of three phase III clinical studies (NCT00596830, NCT00254891, and NCT00254904), and the maximum weight gain in the first 3 months from treatment initiation was categorised as >0%, >2.5%, and >5.0%. Cox proportional hazard modelling of OS was used to estimate hazard ratios (HRs) for each category, including baseline covariates, time to weight gain, and time to confirmed objective response (RECIST Version 1.0). Results Of 1030 patients with advanced NSCLC (IIIB 11.5% and IV 88.5%), 453 (44.0%), 252 (24.5%), and 120 (11.7%) experienced weight gain from baseline of >0%, >2.5%, and >5.0%, respectively. The median time to weight gain was 23 (>0%), 43 (>2.5%), and 45 (>5.0%) days. After adjusting for a time‐dependent confirmed objective response, the risk of death was reduced for patients with any weight gain (>0% vs. ≤0% [HR 0.71; 95% confidence interval-CI 0.61, 0.82], >2.5% vs. ≤2.5% [HR 0.76; 95% CI 0.64, 0.91] and >5.0% vs. ≤5.0% [HR 0.77; 95% CI 0.60, 0.99]). The median OS was 13.5 versus 8.6 months (weight gain >0% vs. ≤0%), 14.4 versus 9.4 months (weight gain >2.5% vs. ≤2.5%), and 13.4 versus 10.2 months (weight gain >5.0% vs. ≤5.0%). Conclusions Weight gain during treatment was associated with a reduced risk of death, independent of tumour response. The survival benefit was comparable for weight gain >0%, >2.5%, and >5.0%, suggesting that any weight gain may be an early predictor of survival with implications for the design of interventional cancer cachexia studies.